Rules on Advertisement in Malaysia - Farhanim, Abdullah Asuhaimi; Nur Amani, Pauzai; Khairun-Nisaa, Asari; Mohd Lotpi, Mohd Yusob (2017)
Advertisement plays an important role in a business activity as it is one of the effective way in marketing strategy. It is important for the seller to provide information on the products or services advertised, its benefit to the consumer and it also help the prospective buyer to make price comparison on the products or services provided by the seller. The advertisement here does not only confine the traditional method of advertising like newspaper and radio, but it also covers Internet advertisement such as Facebook, WeeChat, Instagram and other social media. It became an issue when the advertisement sometime offensive, involve sexual exploitation or even false information was given. It is seems that nobody regulate the advertisement since it is invitation to treat in contract law. Thus, the researchers lay down certain rules and regulations in Malaysia which deals with advertisement. Certain specific sections or rule were also highlighted in the discussion. However, eventhough the regulations were quite extensive, the enforcement still left as a big question when it comes to practice.